Analisis Faktor Demotivasi Belajar Siswa Pasca Pandemi COVID-19 - Nur Rizky Tarigan; Ryzka Aulia; Mhd Syafi’i Saragih; Fauziah Nasution (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
One of the factors that influence the success of student learning is motivation. Motivation is one of the impulses contained in humans to want to do an act in order to achieve certain goals. In practice, distance or indoor (online) learning causes a lot of loss of motivation or demotivation of students as educational objects. According to the findings, prior to the pandemic, the most important characteristics that contributed to a lack of intrinsic motivation in students were low test scores, poor school facilities, learning content and resources, teacher competence and teaching style, and low test scores. On the other side, once the pandemic happened, the most notable variables that were demotivating people were poor test results, insufficient teacher competency and teaching style, inadequate school facilities, learning content and resources, and a lack of intrinsic desire. Keywords: Analition, Demotivation, Pandemi Covid-19